The S447X variant of lipoprotein lipase gene is inversely associated with severity of coronary artery disease - EREN, FATİH (SPRINGER, 2011)
Hyperlipidemia is a major risk factor for coronary artery disease (CAD). Lipoprotein lipase (LPL) is an important enzyme in lipoprotein metabolism. S447X polymorphism of the LPL gene has been implicated in the pathogenesis of CAD. Carriers of X447 allele were reported to have lower triglyceride and higher high-density lipoprotein cholesterol levels as well as a reduced risk of CAD. We hypothesized that S447X gene polymorphism might have a protective effect for CAD. A total of 178 subjects (mean age 42.97 +/- A 6.5 years) who underwent coronary angiography for clinical indications were included in the study. The patients had been referred for evaluation of chest pain and/or abnormal stress tests, and were selected consecutively. Gensini scores were used to assess the severity of CAD; 97 patients were diagnosed with angiographically proven CAD, and 81 subjects did not display significant CAD (a parts per thousand yen70%) angiographically. Genotyping of LPL S447X polymorphism was performed by real-time polymerase chain reaction amplification and fluorescent probe melting point analysis on the light cycler. The minor allele frequencies of LPL 447X allele were 11.1% and 6.2% among subjects without CAD compared with CAD subjects (P = 0.081) and 447X allele had favorable effects on lipid levels among CAD patients; 447X homozygotes and heterozygotes displayed lower total cholesterol (171 +/- A 37 vs 208 +/- A 48 mg/dl, P = 0.02), lower triglycerides (121 +/- A 72 vs 184 +/- A 86 mg/dl, P = 0.02), lower low-density lipoprotein cholesterol (102 +/- A 27 vs 129 +/- A 39 mg/dl, P = 0.03). Gensini scores were significantly lower among the heterozygotes and homozygotes of LPL 447X allele than in the LPL S447 homozygotes (15 +/- A 23 vs 25 +/- A 30, P = 0.048). S447X polymorphism of LPL gene may have a protective role for the severity of CAD. The beneficial effects of S447X polymorphism of the LPL gene may be through its favorable effects on lipid levels.
Keywords: Coronary artery disease severity; Lipids; LPL gene S447X polymorphism; PLASMA-LIPIDS; HDL-CHOLESTEROL; HEART-DISEASE; ATHEROSCLEROSIS; RISK; MUTATIONS; MASS; LPL